Eight Reasons to Prioritize Brain-Computer Interface Cybersecurity. - LÓPEZ BERNAL, SERGIO; HUERTAS CELDRÁN, ALBERTO; MARTÍNEZ PÉREZ, GREGORIO (Communications of the ACM, 2023)
This article discusses the cybersecurity of the brain-computer interface and why it is important to make it a priority. Topics include cyberattack vulnerabilities in new-generation implantable neurostimulation systems, the eight types of cyberattacks that can affect brain behavior, and the impact these attacks could have on the user. [EPC]